Global Bariatric Surgery The Art of Weight Loss Across the Borders (Springer International Publishing, 2018)
This book methodically covers the technique, and results of laparoscopic bariatric and metabolic surgery. Aspiring to be wide-ranging, the content includes developments as well as basic standardized techniques, likely occurring complications, described to help practicians avoid dangerous pitfalls. The editors included such topics as the relationship between obesity and cancer, the use of surgery in adolescents, preparation and follow-up care, as well as the use of interventional radiology. The latest scientific evidence concerning endoscopy, radiology, robotics and pharmaceuticals, is presented in detail. Comprehensive varying opinions on the management of sleeve gastrectomy, weight regain, gastric bypass and complex revisions are unique to this tome. Not only are differing surgical perspectives presented, but physicians, endoscopists and researchers also describe alternative methods of management, in complications, future treatments, and understanding of the disease. Global Bariatric Surgery: The Art of Weight Loss Across the Borders serves as a valuable reference source for surgeons and practitioners in need of the most up-to-date information on bariatric and metabolic surgery with all its known facets. .